Animal Models of Atrial Fibrillation. Issue 1 (19th June 2020) - Schüttler, Dominik; Bapat, Aneesh; Kääb, Stefan; Lee, Kichang; Tomsits, Philipp; Clauss, Sebastian; Hucker, William J.
Abstract : Atrial fibrillation (AF) is the most common sustained arrhythmia encountered in humans and is a significant source of morbidity and mortality. Despite its prevalence, our mechanistic understanding is incomplete, the therapeutic options have limited efficacy, and are often fraught with risks. A better biological understanding of AF is needed to spearhead novel therapeutic avenues. Although "natural" AF is nearly nonexistent in most species, animal models have contributed significantly to our understanding of AF and some therapeutic options. However, the impediments of animal models are also apparent and stem largely from the differences in basic physiology as well as the complexities underlying human AF; these preclude the creation of a "perfect" animal model and have obviated the translation of animal findings. Herein, we review the vast array of AF models available, spanning the mouse heart (weighing 1/1000th of a human heart) to the horse heart (10× heavier than the human heart). We attempt to highlight the features of each model that bring value to our understanding of AF but also the shortcomings and pitfalls. Finally, we borrowed the concept of a SWOT analysis from the business community (which stands for strengths, weaknesses, opportunities, and threats) and applied this introspective type of analysis to animal models for AF. We identify unmet needs and stress that is in the context of rapidly advancing technologies, these present opportunities for the future use of animal models.